Editorial: How multiplexed tools and approaches speed up the progress of metabolic engineering. Issue 5 (2nd May 2013) - Alper, Hal S.; Wittmann, Christoph
<x xml:space="preserve">Abstract</x> Systems metabolic engineering is becoming a widely‐evoked paradigm for industrial strain design and optimization. Specifically, systems wide experimental and computational analyses of cells and their environments enable guide metabolic engineers to quickly parse the genome and creating desirable overproduction phenotypes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>